The best democracy money can buy : an investigative reporter exposes the truth about globalization, corporate cons, and high-finance fraudsters - Palast, Greg (Plume, 2003)
An investigative journalist provides an expose of intrigue, financial misdeeds, and other machinations at the highest level of American politics
مكتبة الشيخ صالح بن عبدا لله المالك [أمين مجلس الشورى السابق
Keywords: Corporations -- Corrupt practices -- United States; Cosmetic techniques; Political corruption -- United States